ANALISIS AKSESIBILITAS DESAIN BANGUNAN PADA GEDUNG MUSEUM KERIS SURAKARTA - Zamzammiyah Nur Aini; Dwi Aries Himawanto (Universitas Mercu Buana, 2018)
Accessibility of museum building is needed for people with disabilities. The purpose of this study is to determine whether there are obstacles and solutions of accessibility problems experienced by people with disabilities in accessing the museum building. Data collection techniques in this study using observation. Data were analyzed using qualitative descriptive analysis technique. The research was conducted at Museum Keris Surakarta. The results show that there are still obstacles related to accessibility problems experienced by disabled people in accessing the museum. So it is necessary to improve the service so that this accessibility problem get the right solution.Keywords: Accessibility, Disabled People, Museum Building